BIOKONTROL JENTIK NYAMUK Aedes aegypti DENGAN PREDATOR IKAN PEMAKAN JENTIK SEBAGAI PENDUKUNG MATERI AJAR INSEKTA - Zen, Suharno (UNIVERSITAS MUHAMMADIYAH METRO, 2012)
Dengue fever is an infectious disease caused by a virus and is transmitted by the Aedes aegypti mosquito. Dengue fever has not yet found a cure and the only prevention is through mosquito vectorÂ control. Health Department policy to prevent and eradicate dengue fever today is to make eradication by means of mechanical, physical, chemical or biological. Biological is one of alternativeÂ control of mosquito vectors that are safe for humans and the environment but still effective in suppressing the mosquito vector. One attempt to do that is by using animals to fight other creatures, or better known as biological control. In the present research was performed using fish of Betta spp, Cyprinus carpio and Oreochormis niloticus as a natural predator of the Aedes aegypti mosquito. The design of this research is Â Completely Randomized Design (CRD) with three treatments are 3 types of fish with 5 times repeated. Data were analyzed with analysis of the range and tested further with the Smallest Real Differences Test (LSD) on the real level 5%. The result of this research is the ability Betta spp eating is higher than the Oreochromis niloticus and Cyprinus carpio by the number of larvae that consumed between 34.6 to 36.9 mosquito larvae tail. The ability to eat at various types of fish against mosquito larvae, influenced by several factors: the agressive, espesialisasi fish to food, the active duration and the amount of time the fish is active in 24 hours.